Taxonomic status and behavioural documentation of the troglobiont Lithobius matulici (Myriapoda, Chilopoda) from the Dinaric Alps: Are there semiaquatic centipedes in caves? - László Dányi; Gergely Balázs; Ivan Hadrián Tuf (ZooKeys, 2019)
Lithobius matulici Verhoeff, 1899 is redescribed based on type material and newly collected specimens. Strandiolus jugoslavicus Hoffer, 1937, described from another cave in the same region in Bosnia and Hercegovina, is presented as a junior subjective synonym of L. matulici (syn. nov.). L. matulici is shown to be most closely related to Lithobius remyi Jawłowski, 1933, type species of the subgenus Thracolithobius Matic, 1962. The completeness of the chitin-lines on the forcipular coxosternite is discussed as a promising character for interspecific differentiation within Lithobiomorpha. Documentation of hitherto unknown semiaquatic behaviour in L. matulici and other cave-dwelling centipede species from Herzegovinian-, Montenegrin- and Pyrenean caves is presented.